“The worst thing that has happened to me”: Healthcare and social services professionals confronting death during the COVID-19 crisis - Hernández-Fernández, Carlos; Meneses-Falcón, Carmen (Frontiers in Public Health, 2022)
Objectives: This study analyzes the emotional impact COVID-19 deaths have had on healthcare, social services, and funeral services professionals, observes the different implications, and analyzes whether professionals who are more accustomed to patient deaths have developed better protection strategies. Methods: This work is based on a qualitative, phenomenological, and interpretative approach through in-depth interviews of 49 informants, including professionals, as well as family members of those who died from COVID-19 in Madrid. The interviews were processed through a qualitative, interpretative, categorical analysis. Results: Healthcare professionals were overexposed to a significant number of deaths under dramatic circumstances. Many professionals had difficulties processing their experiences and expressed the need for psychological help. The fact that certain professionals previously worked with exposure to high mortality rates was not a protective factor. Some coping differences were seen between health care professionals and professionals dedicated to the treatment of the deceased. Conclusion: The overexposure to death with the circumstances that existed during the state of emergency had a significant emotional impact on the professionals that can lead to mental health problems in the near term.